Tick-borne encephalitis virus (TBEV), is the disease still dangerous? - Rogulska, Karolina; Kapczuk, Patrycja; Zioło, Anna; Sarna, Angela; Jacek, Roksana; Grzeszczak, Konrad (Journal of Education, Health and Sport, 2022)
Tick-borne encephalitis virus (TBEV) belongs to the family Flaviviridae. Flaviviruses are 50 nm viruses having a membrane envelope with an RNA genome. The vector of TBEV is the common tick (Ixodes ricinus) prevalent mainly in Europe. Tick-borne encephalitis is endemic in 27 countries in Europe. According to the National Institute of Hygiene, there are several hundred cases per year in Poland. Diagnosis of TBEV may be based on serological tests, molecular tests, cerebrospinal fluid examination. Prevention of tick-borne encephalitis is based on several aspects and the most important are the non-compulsory vaccinations. TBEV is a disease characterised by the risk of many complications, which can be irreversible. Fortunately, thanks to developments in vaccinology, vaccinations are available to prevent infection or reduce the severity of the disease.